Understanding how primary care practitioners can be supported to recognise, screen and initially diagnose oropharyngeal dysphagia: protocol for a behavioural science realist review - Caroline Smith; Sion Scott; Debi Bhattacharya (BMJ Open)
Introduction Oropharyngeal dysphagia (OD) affects around 15% of older people; however, it is often unrecognised and underdiagnosed until patients are hospitalised. Screening is an important process which aims to facilitate proactive assessment, diagnosis and management of health conditions. Healthcare systems do not routinely screen for OD in older people, and healthcare professionals (HCPs) are largely unaware of the need to screen. This realist review aims to identify relevant literature and develop programme theories to understand what works, for whom, under what circumstances and how, to facilitate primary care HCPs to recognise, screen and initially diagnose OD.Methods and analysis We will follow five steps for undertaking a realist review: (1) clarify the scope, (2) literature search, (3) appraise and extract data, (4) evidence synthesis and (5) evaluation. Initial programme theories (IPTs) will be constructed after the preliminary literature search, informed by the Theoretical Domains Framework and with input from a stakeholder group. We will search Medline, Google Scholar, PubMed, EMBASE, CINAHL, AMED, Scopus and PsycINFO databases. We will obtain additional evidence through grey literature, snowball sampling, lateral searching and consulting the stakeholder group. Literature will be screened, evaluated and synthesised in Covidence. Evidence will be assessed for quality by evaluating its relevance and rigour. Data will be extracted and synthesised according to their relation to IPTs. We will follow the Realist and Meta-narrative Evidence Syntheses: Evolving Standards quality and publication standards to report study results.Ethics and dissemination Formal ethical approval is not required for this review. We will disseminate this research through publication in a peer-reviewed journal, written pieces targeted to diverse groups of HCPs on selected online platforms and public engagement events.PROSPERO registration number CRD42022320327.